The heirs his housekeeper carried - Graham, Lynne, 1956- (Graham, Lynne, 1956- Stefanos legacy., 2022)
"Orphaned Leah has never had it easy in life. Desperate for a job, she agrees to become ruthless Giovanni Zanetti's housekeeper and finally gain some security. What she never expected was that being between his billion-dollar sheets would be so undeniably tempting... Gio's night with the totally off-limits innocent was a strictly one-time indiscretion. Anything more than that would require a level of trust he no longer has to give. Then Leah returns with a revelation that rocks the Italian's carefully constructed world: she's pregnant!" -- Page [4] cover.